2017 Polish Diabetological Association Guidelines on Clinical Diabetes Care and what every GP should know about them - Czupryniak, Leszek (Lekarz POZ, 2017)
Since 2004, with yearly updates, the Polish Diabetological Association has been publishing its own guidelines on clinical diabetes care. The article presents this year’s most important recommendations and the changes which were introduced in 2017.